1989
DOI: 10.1136/bmj.298.6670.366
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, job satisfaction, and job stress among general practitioners.

Abstract: Objective-To identify sources of job stress associated with high levels of job dissatisfaction and negative mental wellbeing among general practitioners in England.Design-Multivariate analysis of large database of general practitioners compiled from results of confidential questionnaire survey. Data obtained on independent variables of job stress, demographic factors, and personality. Dependent variables were mental health, job satisfaction, alcohol consumption, and smoking.Setting-National sample of general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
160
2
7

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(178 citation statements)
references
References 9 publications
9
160
2
7
Order By: Relevance
“…This lack of finding is surprising given the research suggesting subjective stress is heightened when on-call from home [27][28][29][30][31]. It is unclear whether this indicates that the hypothalamo-pituitary adrenal axis is not affected or whether, as the authors suggested, it is a consequence of the sampling time utilised in this study [6].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…This lack of finding is surprising given the research suggesting subjective stress is heightened when on-call from home [27][28][29][30][31]. It is unclear whether this indicates that the hypothalamo-pituitary adrenal axis is not affected or whether, as the authors suggested, it is a consequence of the sampling time utilised in this study [6].…”
Section: Discussioncontrasting
confidence: 47%
“…Several studies have shown that being on-call from home results in higher subjective stress levels than when not on-call [6, [27][28][29][30][31]. For example, Sutherland and Cooper [32] showed that doctors found night calls and interruption to family life highly stressful.…”
Section: Introductionmentioning
confidence: 99%
“…Stress in general practitioners (GPs) has been found to be associated with lower job satisfaction and poorer mental health (2 -4). GPs also identify night visits as being particularly stressful (2,5,6). Stressed physicians feel less able to provide quality care (7).…”
mentioning
confidence: 99%
“…informaron la ausencia de relación (7). Lee y Henderson observaron una frecuencia mayor de desgaste profesional en mujeres que en varones (14 el desgaste era mayor en hombres que en mujeres (15). Estas explicaciones están relacionadas con los roles de género (37).…”
Section: Discussionunclassified
“…En otros países se encontró que el desgaste profesional puede afectar entre 14,0 y 63,3% del personal de enfermería (9,10,11,12,13). En diferentes grupos de profesionales, la edad, el sexo, el estado civil, el estrato socioeconómico, el salario y la satisfacción laboral se relacionan con la presencia de desgaste profesional (7,12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionunclassified